SISTEM ANALISA YURIDIS TUGAS KOMITE STABILITAS SISTEM KEUANGAN DALAM PENCEGAHAN KRISIS KEUANGAN DI INDONESIA - Prananingtyas, Paramita (Fakultas Hukum, Universitas Diponegoro, 2017)
Monetary crisis that happened during 1997-1998 had made the Indonesian Government to reform its policy in the monetary system. The most important reformation is in the financial institution. Indonesian government decided to establish a special committee to stabilize the financial system. The legal issue of this paper is the establishment of the Financial System Stability Committee. The purpose of this paper is to understand the reasoning behind the establishment and the operating system of the committee from the point . This is a normative legal research based on secondary sources. This research showed that Financial System Stability Committee based on the Law Number 9 year 2016 on Prevention and Mitigation of Financial System Crisis had to coordinate with its committee member : to preserve and maintain the financial system stability; to handle if the crisis actually happened; to handle the systemic banking problem both in the crisis situation or normal situation.Key words : Bank systemic, financial crisis